Effect of spacings and nitrogen levels on herb and oil yield oil concentration and composition in three selections of Cymbopogon jwarancusa (Jones) Schultz - KOUL, A K DRAW, R SAPRU DHAR, K REKHA, S (Journal of Spices and Aromatic Crops, 1996)
The performance of three selections of Cymbopogon jwarancusa (SL-7822, SL-7869 and SL-7896) was studied under five spacings and two levels of nitrogen. Though herbage and oil yield was higher in 4.01 m' stand density (50 x 50 cm spacing), 1l.l/m' (30 x 30 cm spacing) stand density was preferred as the projected yield per ha was higher in the latter. Increase in nitrogen from 200 to 300 kg/ba did not result in higher herbage and oil concentration in the leaves. The composition of oil was also not affected by spacings or nitrogen levels.